Reviewing on Grammar Learning Strategy Use: A Case Study of EFL Darussalam Polytechnic - Muhammad Bambang Purwanto; Ariya Agustin (Universitas Sarjanawiyata Tamansiswa, 2022)
It was undoubted that studies on grammar instruction have long been discussed. However, there remains a dearth of research on how English as a foreign language (EFL) students learn grammar. Reviewing this line of grammar research, the researchers explored how EFL students experienced grammar learning at Darussalam Polytechnic. The researchers conducted a qualitative multiple case study and used semi-structured individual interviews as the main instrument for data collection in this study. EFL students were interviewed regarding their views on the role of grammar and their use of grammar learning strategies. Grounded on pedagogies of grammar instruction, the study showed that most participants still learned English grammar through the traditional approach, i.e., grammar instruction. Findings from the inductive content analysis indicated that all participants acknowledged the essential role of grammar in learning English, and demonstrated a strategic approach to grammar learning, with environmental and behavioral management and cognitive strategies being the most popular strategies. The findings can help English teachers adjust their teaching approach and techniques to maximize students’ grammar achievement and enhance their effective grammar learning strategies for long-term benefits. The study contributes to research on Asian EFL students’ attitudes toward grammar learning and their use of grammar learning strategies.